PTU-051 Day case 'treat and transfer' ercp service under general anaesthesia. (17th June 2017) - El-sherif, Y; Hunt, J; Suddle, A; Prater, B; Reffitt, D; Devlin, J; Harrison, P; Joshi, D
Abstract : Introduction: General Anaesthesia (GA) has been increasingly used for advanced endoscopic procedures in particular ERCP (endoscopic retrograde cholangio-pancreatography). Given the increasing pressure on many hospitals, the delivery of such service on a regular basis may not always be possible. We established a new day case "treat and transfer GA ERCP" service at Kings College Hospital (KCH), NHS Foundation Trust, London, UK. The new service allows local hospitals to transfer inpatients requiring urgent GA ERCP to KCH endoscopy unit for a day case GA ERCP procedure. Patients are discharged back to their referring hospitals after four hours observation period post completion of ERCP. We describe our experience in evaluating the safety and overall feasibility of this new service. Method: Database has been prospectively interrogated for all adult inpatients who were referred to KCH endoscopy unit for urgent ERCP under GA during the period from March 2015 to December 2016. We documented patients' demographics, ERCP indications, American Society of Anaesthetists (ASA) status, Cotton grade of endoscopic difficulty and endoscopic and anaesthetic complications. Results: 61 patients were referred to endoscopy unit at KCH for urgent day case GA ERCP from nine referring hospitals. The main indications were failed ERCP under conscious sedation 46% (28/61), and unavailability of GA ERCP list locally 43% (26/61). 3 patients were cancelled by their local hospitals (2 patients were unstable for transfer and 1 patient required full inpatient transfer to KCH liver ITU due to progressive deterioration). After exclusion of cancelled referrals, a total of 58 ERCPs patients were transferred to KCH endoscopy unit; 64% (37/58) females with median age 57 years (range 23-90). 76% (44/58) of patients had a virgin papilla, with 39% (23/58) of patients were ASA 3 or greater. The Cotton Grade was 3 or more in 50% (29/58) of patients. ERCP was performed on all patients and completed successfully in 86% (50/58). For patients with previous failed ERCP, repeat ERCP under GA was successful in 71% (20/28). ERCP was not completed in 8 patients (anatomical distortion=5 and failed cannulation=3). All patients were safely discharged back to their referring hospitals after the short observation period post-ERCP. No complications related to anaesthesia or endoscopy were reported peri- or post- procedure. Conclusion: Urgent inpatient transfers between hospitals for performing ERCP under GA as a day case is safe and feasible. The new GA ERCP pathway can be replicated by other UK centres. Disclosure of Interest : None Declared